Absolute continuity in partial differential equations - Farjudian, Amin; Emamizadeh, Behrouz (Michigan State University Press, 2015)
In this note we study a function which frequently appears in partial differential equations. We prove that this function is absolutely continuous, hence it can be written as a definite integral. As a result we obtain some estimates regarding solutions of the Hamilton-Jacobi systems.